PENGARUH ANTARA KEPEMILIKAN KELUARGA DAN CORPORATE GOVERNANCE TERHADAP TINDAKAN PAJAK AGRESIF - Nur Hidayanti, Alfiyani; Laksito, Herry (Diponegoro Journal of Accounting, 2013)
This study aims to analyze and provide empirical evidence of influence between family ownership and corporate governance for aggressive action.The hypothesis (1) family ownership affect aggressive tax measures, (2) corporate governance affects aggressive taxation.The population in this study is a manufacturing company listed on the Stock Exchange 2008-2011.Data was collected using purposive sampling method for manufacturing companies listed on the Indonesia Stock Exchange. Data were analyzed using regression analysis.The results of this study indicate that family ownership has no significant effect on aggressive tax measures. While corporate governance has a significant effect on aggresive tax measures as measured by cash effective tax rate (CETR).